Therapeutic Effect of Doxorubicin-Chlorin E6-Loaded Mesoporous Silica Nanoparticles Combined with Ultrasound on Triple-Negative Breast Cancer - Xu P (Dove Medical Press, 2020)
Peng Xu,1,2,* Jia Yao,1,* Zhen Li,3,* Meng Wang,2 Linghui Zhou,1,2 Guansheng Zhong,1 Yi Zheng,1,2 Na Li,1,2 Zhen Zhai,1,2 Si Yang,1,2 Ying Wu,1,2 Dai Zhang,2 Zhijun Dai1 1Department of Breast Surgery, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou 310003, People’s Republic of China; 2Department of Oncology, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an 710004, People’s Republic of China; 3Department of Student Affairs, The Second Affiliated Hospital of Xi’an Jiaotong University, Xi’an 710004, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhijun DaiDepartment of Breast Surgery, The First Affiliated Hospital, College of Medicine, Zhejiang University, Hangzhou 310003, People’s Republic of ChinaTel +86 571 8723 6852Email dzj0911@126.comIntroduction: Sonodynamic Therapy (SDT) has good targeting and non-invasive advantages in solid cancers, but its antitumor effect is not sufficient to replace traditional treatments. Some studies that combined SDT with chemotherapy or nanoparticles have managed to enhance its efficiency and overcome the side effects of chemotherapy.Materials and Methods: In this study, we synthesized and characterized mesoporous silica nanoparticles (MSN-DOX-Ce6) loaded with doxorubicin (DOX) and sonosensitizer, chlorin e6 (Ce6). Then, we conducted in vitro and in vivo experiments to explore the antitumor effect of MSN-DOX-Ce6 under ultrasound (US) treatment.Results: The characterization tests showed that the nanoparticles are uniformly sized spheres with mesoporous structure, resulting in a high drug-loading efficiency. In the in vitro experiments, MSN-DOX-Ce6 could effectively inhibit cell proliferation under US but not more than other treatment groups. However, the in vivo studies showed that MSN-DOX-Ce6+US has better antitumor effect than DOX+Ce6+US or DOX alone on xenograft tumor-bearing mice.Conclusion: In summary, MSNs showed a great potential for DOX and Ce6 delivery. We concluded that under US, MSN-DOX-Ce6 nanocomposites increase the antitumor effect of DOX and SDT and thereby are a potential treatment for solid tumors.Keywords: sonodynamic therapy, co-delivery, combination chemotherapy, nanomaterials